Design of high-efficiency electromagnetic energy harvester based on a rolling magnet - Zhang, L. B. (2021)
Ambient vibrations resulted from mechanical motions and body movements are ubiquitous in daily life, which contain substantial amount of energy that can be converted into electricity by electromagnetic conversion. However, most existing electromagnetic energy harvesters utilize sliding or rotating magnets cutting the coil to produce electric current. Here an energy harvester using a rolling magnet is designed and fabricated, which can significantly increase the magnetic flux rate when cutting the coil compared to that using a sliding magnet. Importantly, a friction effect is introduced to improve the energy harvesting performance for this design, the output average power has been further increased by 50%. Experimental results show that under a walking speed of 4 km/h, an average power of 0.5 mW can be produced. While in the experiments of hand shaking with a frequency of 3.1 Hz, an average power of 1.02 mW can be captured. It is observed that the electric energy harvested from one-minute hand shaking is able to operate a sensor with 1.1 V working voltage for about two minutes. The conducted experiments of energy harvesting from walking/running, hand shaking and cycling demonstrate great potential of the developed harvester in building up self-powered wearable sensing systems.